Psychiatric referrals to the general hospital emergency department: are we being effective? - Keller, Shikma; Tilbor, Einat; Shwiki, Afnan; Florentin, Sharon; Laufer, Sofia; Bonne, Omer; Canetti, Laura; Reuveni, Inbal (Frontiers in Psychiatry, 2023)
Introduction: General hospital emergency departments (GHEDs) are notoriously overcrowded. This is caused, in part, by ineffective referrals, that is to say referrals that do not require medical examination or other interventions in the context of a general hospital. This study aims to investigate the contribution of psychiatric referrals to this issue, to identify potential determinants of these referrals and offer means to reduce them. Materials and Methods: Retrospective data were collected from psychiatric admission files within a GHED of a tertiary-care city hospital over a one-year period. Two experienced clinicians separately reviewed each file to determine rationale of referrals according to predetermined criteria. Results: A total of 2,136 visits included a psychiatric examination, 900 (42.1%) were determined 'effective', and 1,227 (57.4%) were deemed 'potentially ineffective'. The leading causes for potentially ineffective referrals to a GHED were psychiatric illness exacerbation (43.4%), and suicidal ideations (22%). Most referrals (66.9%) were initiated by the patient or their family, and not by a primary care physician or psychiatrist. Conclusions: Nearly half of the psychiatric referrals did not necessarily require the services of a general hospital, and may be more suitable for referral to a dedicated psychiatric facility. Ineffective referrals to the GHED pose a burden on general hospital resources, and may be less effective for the psychiatric patients. This calls for clear guidelines for the provision of optimal emergency treatment for mental-health patients.